2019
DOI: 10.1111/imr.12760
|View full text |Cite
|
Sign up to set email alerts
|

Secrets and lyase: Control of sphingosine 1‐phosphate distribution

Abstract: SummaryThe signaling lipid sphingosine 1‐phosphate (S1P) plays key roles in many physiological processes. In the immune system, S1P's best‐described function is to draw cells out of tissues into circulation. Here, we will review models of S1P distribution in the thymus, lymph nodes, spleen, and nonlymphoid tissues. These models have been challenging to construct, because of the lack of tools to map lipid gradients. Nonetheless, evidence to date suggests that S1P distribution is exquisitely tightly controlled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 126 publications
0
10
0
Order By: Relevance
“…In lung-transplanted CF patients, plasma levels of unbound S1P were lower than control subjects, and relevant differences were measured depending on the genotype of CF patients [ 10 ]. S1P concentration is normally elevated in blood and lymph, and low in tissues [ 39 , 40 ]. This gradient is finely tuned by a complex equilibrium between synthesizing and catabolizing enzymes, together with transporter proteins that regulate S1P passage across the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In lung-transplanted CF patients, plasma levels of unbound S1P were lower than control subjects, and relevant differences were measured depending on the genotype of CF patients [ 10 ]. S1P concentration is normally elevated in blood and lymph, and low in tissues [ 39 , 40 ]. This gradient is finely tuned by a complex equilibrium between synthesizing and catabolizing enzymes, together with transporter proteins that regulate S1P passage across the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of the S1P Transporter Spns2, which is known to export S1P and thereby reduces intracellular S1P, abolishes the strong induction of MCP‐1 by TNF‐α and IL‐1β in the human renal proximal tubular epithelial cells [37]. S1P mainly acts through five high affinity G protein‐coupled S1P receptors, which are ubiquitously expressed and mediate a complex network of signaling in a cell type dependent manner [38, 39]. In fact, our previous study has demonstrated that S1P leads to the up‐regulation of MCP‐1 mRNA and protein via S1P receptor 2 and 3 in BMMs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine 1-phosphate (S1P), a product of cell membrane sphingolipid catabolism, is a pleiotropic mediator involved in a variety of cellular functions such as adhesion, migration, inflammation, and proliferation in many cell types (7)(8)(9). S1P is generated from sphingosine intracellularly by sphingosine kinases 1 and 2 (SphK1 and SphK2).…”
Section: Introductionmentioning
confidence: 99%